Fundamentals of corporate finance - Ross, Stephen A,Westerfield, Randolph,Jordan, Bradford D
Fundamentals of corporate finance / Stephen A Ross, Randolph Westerfield, Bradford D Jordan .- New York, NY : McGraw Hill Education , 2016 .- 913 p. ; 26 cm .- 9780077861704